'Smart, clued-in guys': Irish rugby players as sporting celebrities in post-Celtic Tiger Irish media. (1st June 2018) - Free, Marcus
Ireland's 'Celtic Tiger' economic boom ended with the 2008 global financial crisis. There followed a series of severe 'austerity' budgets and public service pay deals involving cuts in public service provision and employment reform. These were accompanied by approving Irish media narratives of atonement for Celtic Tiger 'excess' and, more recently, of corresponding 'recovery' through collective and individual discipline and entrepreneurial endeavour. This article focuses on the interplay between Irish media narratives of austerity and recovery and constructions of gender, class and national identity in representations of rugby players as celebrities. It explores how elite players have been presented as exemplary of the neo-liberal management of physical and economic risk, and how the repeated focus on successful struggles with diet and injury and post-career educational and business investments highlights their optimizing of the physical and social capital afforded by celebrity status. The emphasis on discipline and 'smart' economic management chimes with the hegemonic political and media discourse of 'no alternative' government austerity, and with economic recovery through individual acceptance of responsibility.